2016
DOI: 10.1093/ee/nvv224
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Differentiation AmongAnastrepha fraterculus(Diptera: Tephritidae) Exploiting Sympatric Alternate Hosts

Abstract: Anastrepha fraterculus (Wiedemann) is currently considered a complex of cryptic species infesting fruits from Mexico to Argentina and represents an interesting biological model for evolutionary studies. Moreover, detecting and quantifying behavioral, morphological, and genetic differentiation among populations is also relevant to the application of environment-friendly control programs. Here, phenotypic differentiation among individuals coexisting in the wild in a Northern region of Argentina was unveiled and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
1
8
0
2
Order By: Relevance
“…In Argentina, sympatric population of A. fraterculus showed microdifferentiation due to host use, which was revealed in morphometric and genetic variability (Gómez-Cendra et al 2016). Colombian populations of the Andean morphotype of this species show microevolutionary processes like Argentinian populations; however, Colombian populations are allopatric.…”
Section: Discussionmentioning
confidence: 95%
“…In Argentina, sympatric population of A. fraterculus showed microdifferentiation due to host use, which was revealed in morphometric and genetic variability (Gómez-Cendra et al 2016). Colombian populations of the Andean morphotype of this species show microevolutionary processes like Argentinian populations; however, Colombian populations are allopatric.…”
Section: Discussionmentioning
confidence: 95%
“…Gomez-Cendra et al (2016) found that it was not geographical distance that affected the wing morphology of their fruit flies, but the host fruit available to the flies, those feeding on the same fruit had similar wing morphology no matter how far apart they lived. Using molecular markers and noting phenotypic differentiation, Gomez-Cendra et al (2016) reported that flies collected from and feeding on peaches or walnuts differed genetically and in appearance from each other regardless of geographical or temporal overlap. Yi Bai found that the grasshopper species Trilophidia annulata followed the Bergmann rule where individuals from higher, cooler latitudes with longer growing seasons were larger in size (using wing length as a measure) than individuals from the lower, warmer latitudes (Yi Bai et al 2016).…”
Section: Introductionmentioning
confidence: 95%
“…The wing morphology of two sibling Drosophila species was influenced by the different host plants (cactus) they fed on (Carreira et al 2006;Soto et al 2008Soto et al & 2010. Gomez-Cendra et al (2016) found that it was not geographical distance that affected the wing morphology of their fruit flies, but the host fruit available to the flies, those feeding on the same fruit had similar wing morphology no matter how far apart they lived. Using molecular markers and noting phenotypic differentiation, Gomez-Cendra et al (2016) reported that flies collected from and feeding on peaches or walnuts differed genetically and in appearance from each other regardless of geographical or temporal overlap.…”
Section: Introductionmentioning
confidence: 95%
“…Número de fêmeas e machos emergidos (♀♀, ♂♂). Selivon et al 2004Selivon et al , 2005aSelivon et al , 2005bCha et al 2012;Powel et al 2014;De Meyer et al 2015;Gomes-Cendra et al 2016;Ragland et al 2016).…”
Section: Iv3 Perturbações Ontogenéticas Associadas Ao Estresse Da Tunclassified
“…Essa variação morfológica proporcionou um considerável nível de discriminação entre os indivíduos criados em diferentes plantas hospedeiras, principalmente os provenientes de goiaba. Esses resultados vão de acordo com os encontrados por Gomes-Cendra et al (2016), que analisaram seis medidas morfométricas (sendo duas medidas da asa) de A. sp.1 provenientes de três diferentes hospedeiros (goiaba, noz e pêssego) coletados em simpatria, na região norte da Argentina. Vários estudos também detectaram plasticidade fenotípica associada ao hospedeiro em outros grupos de insetos, alguns exemplos são a mariposa Ectomyelois ceratoniae (Mozaffarian et al 2007), as moscas dos cactos Drosophila gouveai e D.…”
Section: Iv3 Perturbações Ontogenéticas Associadas Ao Estresse Da Tunclassified